Transient solidification and melting numerical simulation of lauric acid PCM filled stepped solar still basin used in water desalination process - Fayaz, Hussain; Shaik, Saboor; Khan, Sher Afghan; Huynh, Van Van; Jilte, Ravindra D.; Sundara, Vikram; Asif, Mohammad; Linul, Emanoil (Elsevier Ltd, 2023)
It is crucial to produce potable water from salt water in arid places using a stepped solar still desalination process. This work presents lauric acid PCM's temperature distribution and phase transformation in an inclined stepped solar still desalination system. A second-order finite volume method is employed for discretizing the two-dimensional geometry. At the same time, energy, continuity, and momentum equations are solved and then coupled using the second-order PRESTO algorithm. The solidification and melting CFD models have been used to capture the melting stages of lauric acid PCM. Four steps with an inclination of 300 to ground and two different cases with saline water levels of 10 mm and 40 mm have been reported. The results reveal that the temperature and mass fraction of lauric acid PCM strongly depends on the saline water level at each step, the number of steps, the angle of inclination, and the location of the solar still step. The maximum percentage increase in PCM melting fraction is 50%, and a PCM temperature rise of 4oC is observed in the case of SWL-max compared to SWL-min. The total enthalpy of lauric acid PCM is increased by 30% for the SWL-max water level compared to the SWL-min water level.